Impact of TyG index on coronary plaques in patients with coronary artery disease under aggressive lipid-lowering therapy - Fukase, Tatsuya; Dohi, Tomotaka; Takahashi, Norihito; Doi, Shinichiro; Okai, Iwao; Iwata, Hiroshi; Okazaki, Shinya; Miyauchi, Katsumi; Daida, Hiroyuki; Minamino, Tohru (Frontiers in Endocrinology, 2026)
BackgroundOne of residual risks of coronary artery disease (CAD) occurrence and coronary plaque progression might be a triglyceride-glucose index (TyG index). Thus, this study aimed to investigate the impact of TyG index on coronary artery plaques detected by serial intravascular ultrasound (IVUS) in patients with CAD under low-density lipoprotein cholesterol (LDL-C) lowering therapy represented by statins. MethodsThis observational cohort study included three clinical prospective trials (the ENTERPRISE trial, ESPECIAL-ACS study, and ZEUS trial) in which coronary plaques were assessed using serial grayscale IVUS at baseline and at 6–12 months follow-up. The patients were divided into two groups according to the cutoff value of baseline TyG index (dichotomized to ≥ or <8.5) based on a previous report. The primary endpoint was defined as an absolute change in percentage atheroma volume (PAV) from baseline to follow-up. ResultsA total of 131 patients (mean age: 63 years; 92% men) completed the study and were analyzed. Compared to the low TyG index group, the high TyG index group had higher body mass index, triglyceride, and proportion of male, diabetes mellitus, and smoking history, as well as lower high-density lipoprotein cholesterol; whereas, there was no difference in LDL-C between both groups. The absolute change in PAV between the low TyG index group and high TyG index group only in patients who received aggressive lipid-lowering therapy (LLT) was −3.5±1.4% by analysis of covariance (p=0.017). In addition, the baseline TyG index, male, and %change in LDL-C were significantly associated with the absolute change in PAV under aggressive LLT by multiple linear regression analysis. ConclusionsAn elevated TyG index could be a residual risk of coronary plaque progression under aggressive LLT.